Community member perceptions of influences on teenage pregnancies. Issue 5 (28th October 2016) - Phaswana-Mafuya, Nancy; Tabane, Cily; Davids, Adlai
Abstract : This exploratory qualitative study aimed to provide insight into the factors contributing to the high prevalence rate of teenage pregnancy in South African communities. Focus group were conducted with 193 community members (females = 44.6%; adults = 50.8%, teenagers/youth = 44.0%) and followed by thematic content analysis to interpret the data. Several overarching themes regarding the increasingly common occurrence of teenage pregnancy emerged from the data. These included: (1) the increased acceptability of teenage pregnancy to families and communities for economic and material gain; (2) the influence of social pressure; and (3) the lack of sexual knowledge and provision of sex education. Community members perceived teenage pregnancy as an increasingly common occurrence in their communities. Community members perceived teenage pregnancy to be driven by multiple factors and to require holistic interventions at the individual, family and community level.